Children’s Languge Development Through Audio Visuao Media Age 5-6 Years In Kidergarten Islam Ibnu Qoyyim Setia Budi - Siregar, Isopil (EDU-RILIGIA: Jurnal Ilmu Pendidikan Islam dan Keagamaan, 2024)
Study this is purposeful For know developments Language child with using the Storytelling Method with Audio Visual Media 5-6 years old at Ibnu Islamic Kindergarten Qoyyim Medan Selayang Setia Budi Medan District. This research method uses observation, interviews and documentation. This research uses collection analysis data, data reduction, data display and drawing conclusions from research. Research findings shows (1) language development The school uses the storytelling method and using audio-visual media in the form of images, TV, radio and video in every child's learning. (2) Children's language development at the Ibnu Islamic Kindergarten school Qoyyim develop with Good can seen from results study 8 from 10 child Which in thorough experience development Language Which very Good And showed with sheet observation Which flat flat child own mark Which satisfying. (3) use media it turns out impact positive on child, seen that media audio visual Which in for by Teacher can interesting attention they And can make child concentrate with What Which He Look. Apart from that, by using this audio visual media, the message is conveyed through The story can be accepted by children well. Barriers to using audio visuals is, limitations a simple video that can be used to convey message to child.